Cinematic Code of Short Prose - Nikoriak, Nataliia; Матійчак, Альона (International scientific journal «Grail of Science», 2022)
The paper is motivated by new perspectives in expending the boundaries of the literary text analyses in the aspect of intermediality theory. The short story "Freeze-Frame" by Tatiana Belimova from the collection "Rose Jam" (2015) is examined in the context of intermedial studies. The relevance of the paper is emphasized by new attitude to the interplay between different arts. The analysed text is a bright contemporary example of the active interaction between literature and cinema, where cinema manifests itself not only in terms of subject matter and personosphere. Respectively, the key techniques of film poetics (retrospection, editing, framing, medium and close-up, detailing) are built into the structure of the traditional literary genre, presenting, at the same time, a kind of cross-genre experiment, which allows to consider Belimova's short story as a sample of film narrative. The findings support that these techniques allow to reveal new receptive and interpretive properties of the literary text and to study in depth the specifics of the "intermedial vision" of the writer.
Keywords: intermedial poetics, cinematic code, film narrative, "Freeze-Frame".